(untitled) (Società e diritti, 2025)
The transition from the use of certificates to that of self-declarations, in relations between private individuals and the public administration, does not seem to be complete due to the presence of technical gaps and unresolved legal issues, highlighted by administrative practice that is still resistant to decertification. Even though this process began in the second half of the last century and the legislation has been the subject of multiple interventions by the legislator up to the present day, the long-standing problems regarding the effectiveness of self-certification institutions and the doubts regarding the legal status of citizens in relations with the public administration persist. In this context, the study intends to examine the scope and limits of the rules on the simplification of administrative documentation, in search of a genuine right to self-certification.